2017
DOI: 10.1057/s41260-017-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of plan and sponsor characteristics on pension funds’ asset allocation and currency diversification

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The model attempts to control for the impact of risk on flow by the annualized standard deviation of the monthly pension fund returns of the past 12 months. Additionally, size could affect the flow-performance relationship (Chevalier and Ellison, 1997) and improve diversification (Defau and Moor, 2017). DelGuercio and Tkac (2002) argue that the presence of a significant relationship would signal the importance of agency relationship or client servicing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model attempts to control for the impact of risk on flow by the annualized standard deviation of the monthly pension fund returns of the past 12 months. Additionally, size could affect the flow-performance relationship (Chevalier and Ellison, 1997) and improve diversification (Defau and Moor, 2017). DelGuercio and Tkac (2002) argue that the presence of a significant relationship would signal the importance of agency relationship or client servicing.…”
Section: Methodsmentioning
confidence: 99%
“…Size could also contribute to the visibility of the fund and signal a better reputation (Jain and Wu, 2000; Sapp and Tiwari, 2004; Alves and Mendes, 2010). Investors could also be choosing large plans for risk reduction through better diversification, as documented by Defau and Moor (2017). Visibility and reputation could also change with the age of the pension plan and affect the fund inflows.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, he argues that in the absence of taxes, risk-sharing, and default insurance, the allocation to equity versus debt is determined solely by the risk-return preferences of the trustee and/or the employer. Similarly, Defau and de Moor (2018) find that employers (employees) that pay higher contributions to pension tend to have a higher (lower) allocation to risky assets. In addition, to fund characteristics, research has also shown that regulatory framework is also a determinant in pension fund asset allocation.…”
Section: Introductionmentioning
confidence: 91%
“…Finally, we have also included the pension funds' total assets in our analysis, since previous authors concluded that larger pension funds invest more in risky assets. For a comprehensive overview of this literature, see Defau and De Moor (2018). In Table 4, we present the average pension fund size per year in million dollars.…”
Section: Datamentioning
confidence: 99%